Is it Enough? An Analysis of the Living Conditions of Left-Behind and Migrant Children Receiving Cash Transfers in Qinghai and Anhui Provinces of China - Jianping Yao; Robert Walker (East Asian Journal of Multidisciplinary Research, 2023)
Children are often negatively affected by large-scale rural-urban migration. This study examines the effects of cash transfer payments on left-behind children and migrant children and explores the adequacy of child cash transfer programs. Multivariate regressions were performed to examine the effects of child cash transfer benefit on two types of children using the data were from European Union and Sida granted project. We found while the transfer increased the incomes of recipient households, the living condition of children measured by meals, transportation to school, clothing expenditure, socializing expenditure, and self-reported adequacy remained disproportionately low compared with their no-transfer neighbors. The study suggests the multidimensional poverty experienced by children affected by migration requires multifaceted policy solutions.